THE APPLICATION OF INQUIRY-BASED LEARNING TO IMPROVE STUNDETS’ SPATIAL CAPABILITY IN SMA YPK MEDAN - Narpila, Suci Dahlya (JPI (Jurnal Pendidikan Indonesia), 2018)
This study stems from the writer's anxiety about the low ability of spatial students in SMA YPK Medan. The low spatial ability was caused by the ineffectiveness of the learning applied by the teacher. The purpose of this study was to describe the data of students' spatial ability improvement as a result of the application of inquiry learning model. This research was a quasi experimental research with a design used was pretest posttest control group design. The sample of this research were 69 students of SMA YPK Medan. Data to be collected in this research was the data of students' spatial ability. The instrument used to collect the data was a spatial ability test. The data were collected then analyzed by using one-way ANOVA in SPSS program. From result of SPSS obtained data Fcount> Ftable, that is 8,945 > 3,973 and Sig. < , that is 0,04 < 0,05. Based on the results of data analysis could be concluded that the improvement of spatial ability of students who received inquiry learning was higher than the improvement of spatial ability that gets regular learning.